Railway Engineering Science - Zhai, Wanming; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer.)
Railway Engineering Science is an international, peer-reviewed, and free open-access journal that publishes original research articles and comprehensive reviews related to fundamental engineering science and emerging technologies in rail transit systems, focusing on the cutting-edge research in high-speed railway, heavy-haul railway, urban rail transit, maglev system, hyperloop transportation, etc. The main goal of the journal is to maintain high quality of publications, serving as a medium for railway academia and industry to exchange new ideas and share the latest achievements in scientific research, technical innovation and industrial development in railway science and engineering. The topics include but are not limited to Design theory and construction technology System dynamics and safety Electrification, signaling and communication Operation and maintenance System health monitoring and reliability Environmental impact and sustainability Cutting-edge technologies The publication costs for Railway Engineering Science are fully covered by Southwest Jiaotong University so authors do not need to pay any article-processing charges.
Keywords: Automotive engineering; Engineering geology; Regional economics; Spatial economics; Automotive Engineering; Geoengineering; Regional and Spatial Economics